An analysis of ELT coursebooks in terms of 21st century skills (Journal of Educational Sciences, 2021)
With the advances in innovation in the 21st century, the abilities needed to be effective in life have extensively changed. English, as a school subject, has assumed a main part in executing large numbers of the instructive changes and new methodologies in teaching since it is a worldwide language. Coursebooks, being a significant part of the educating and learning measure, impressively affect joining new methodologies into their schedules. Therefore, the current study aims to examine the 4Cs of 21st Century Skills – communication, collaboration, critical thinking, creativity, in English language teaching coursebooks. In view of this reason, a qualitative method – content analysis design – was employed. The data was collected through internal and external evaluation checklists, which were developed based on related literature and field experts’ opinions. The scope of the study was three 9th grade coursebook series designed by international publishing companies, namely English Plus by Oxford University, Excel by Express Publishing and Fall Blast by MM Publications. These coursebooks were chosen because these books are chosen by MES of RK and used in all schools. As the researcher works at school and teachers the 9th grade namely the 9th grade is taken for this study.  According to the results of the study, it has been revealed that each coursebook series includes the 21st century skills to some extent mostly in project, speaking and writing tasks. According to the findings it was also revealed that there are limited number of outcomes in relation to creativity, responsibility, social and flexibility and adaptability skills. Furthermore, there are not any outcomes related to information literacy, innovation, problem-solving, media literacy, ICT, cross-cultural skills, productivity and accountability, initiative and self-direction and leadership.Keywords: 21st сentury sills, communication, collaboration, critical thinking, creativity, coursebook analysis, evaluation, ELT coursebooks.